2013
DOI: 10.15294/komunitas.v5i1.2381
|View full text |Cite
|
Sign up to set email alerts
|

Kontekstualisasi (Pendidikan) Antropologi Indonesia

Abstract: Dunia pendidikan Indonesia saat ini berada dalam kondisi yang ambivalen. Pendidikan yang seharusnya dapat secara positif membekali manusia dengan modal pengetahuan praktis maupun substantif yang berguna justru mempunyai potensi yang sebaliknya, yaitu menjadi kendala bagi pembangunan berkelanjutan karena tuntutan-tuntutan praktis, khusus, dan sesaat yang dikehendaki oleh kepentingan-kepentingan ekonomi, politik, dan sosial yang selalu berubah. Fakta tersebut menjadi latar belakang penulisan artikel ini yang ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The findings from the study also corroborate those of Yusoff (2011) exploration on the relationship between Malaysian corporations' organizational culture and financial performance which found that all four dimensions of culture (power distance, avoidance of uncertainty, individualism and manhood) used in the research had affected the ROA and EPS, but the ROA and EPS were positively influenced by only one compound (uncertainty avoidance). This trend was also observed in Laksono's (2013) research on effect of corporate culture on Indonesia's corporate performance in which the findings demonstrated the important impact of corporate culture on corporate success.…”
Section: Modelsupporting
confidence: 68%
See 1 more Smart Citation
“…The findings from the study also corroborate those of Yusoff (2011) exploration on the relationship between Malaysian corporations' organizational culture and financial performance which found that all four dimensions of culture (power distance, avoidance of uncertainty, individualism and manhood) used in the research had affected the ROA and EPS, but the ROA and EPS were positively influenced by only one compound (uncertainty avoidance). This trend was also observed in Laksono's (2013) research on effect of corporate culture on Indonesia's corporate performance in which the findings demonstrated the important impact of corporate culture on corporate success.…”
Section: Modelsupporting
confidence: 68%
“…The rationale behind this adoption is that corporate culture has a positive influence on policies and strategies and therefore creates a sustainable competitive advantage over competitors. Laksono (2013) focused on the effect of corporate culture on Indonesia's corporate performance. In the Structural Equation Modeling (SEM), data were analyzed from 151 institutions.…”
Section: Organizational Culture and Firm Performancementioning
confidence: 99%
“…In the case of the treatment mantra above, the vowel used is the independent vocal process, which is recited by the shaman himself. This combination of literary language and vocal process makes the beauty of the sound listened by listeners [11].…”
Section: ) Mantra Ubek Sakik Mato (Eye Painmentioning
confidence: 99%